Locoregional Anesthesia for Major Abdominal Surgeries during COVID-19 Outbreak: An Experience in a Tertiary Care Hospital of Kathmandu, Nepal - Basukala, Sunil; Mishra, Raveesh; Gautam, Alok Raj; Basukala, Bikram; Karki, Saurav (Annapurna Journal of Health Sciences, 2023)
Introduction: Locoregional Anesthesia (LA) has many benefits over general anaesthesia in major abdominal surgeries with high risks including avoidance of endotracheal intubation thus avoiding aerosol contamination during coronavirus disease 2019 (COVID-19). Methods: A retrospective analysis was performed among patients undergone major abdominal surgery under loco regional anesthesia during April 2019 and March 2020 in 750 bedded tertiary care hospital during COVID- 19 pandemic. In all cases, locoregional anesthesia (spinal, epidural, or combined spinal-epidural anesthesia) was performed. Intraoperative and postoperative complications were monitored and was analyzed. Results: A total of twenty-four cases were included during the study period. Among the cases, majority of cases belonged to gastrointestinal, n=17(70.83%). The mean operative time was 94 minutes (minimum 55 minutes; maximum 168 minutes). None of the cases required conversion to general anesthesia. Postoperative pain was always well controlled. None of them required postoperative intensive care support. No perioperative major complications (Clavien–Dindo ≥3) occurred. Three cases were found to be infected with COVID -19 infection postoperatively.Conclusion: Our study showed that major abdominal surgeries under loco regional anesthesia resulted feasible, safe, painless, and, in specific cases, was the only viable option. In such a pandemic, it could become a vital strategy to avoid contamination among Health care workers (HCWs) and could limit viral transmission inside theatres.